E-Learning Implementation as a Support Teaching Learning Processes for Lecturers and Students in Universitas Pembangunan Nasional “ Veteran” Jawa Timur - Nuruni I. K.W; Sishadiyati; Zumrotul F. (Nusantara Science and Technology Proceedings)
Current technological developments are increasingly advanced and sophisticated both in education and business. With the development of these technologies, it is expected that in the University of East Java's National Development in the teaching and learning process can also implement by following the development of these technologies. In the environment of UPN "Veteran" East Java, the campus management has provided a web-based or online learning system, namely E-learning. With the E-learning system, the researchers want to know how much the E-learning system is used among lecturers and students. To find out about this, researchers conducted research using the PIECES method with the instruments used were Performance, Information, Economic, Control, Efficiency, and Service. From the results of the PIECES method it was found that the use of the E-learning system in the teaching and learning process in the environment of UPN "Veteran" East Java can still be said to be less used by lecturers and students by looking at the average value of all aspects in the PIECES method of 67.36 %. It can be said that the lack of socialization to lecturers and students about the benefits of using E-learning systems in the world of education, especially for the teaching and learning process.